Effect of Blood Flow Restriction Combined with Low Intensity Resistance Exercise on Cardiorespiratory Aerobic Endurance and Exercise Ability in Adolescent Swimmers - Ma Mengyin; Liu Zhaozhi; Xu Kuo; Lang Jun (International Journal of Education and Humanities, 2025)
Objective: To compare the effects of blood flow-restricted resistance training (BFR-RT) and conventional resistance training on cardiorespiratory function and exercise capacity in adolescent swimmers. Methods: Sixteen adolescent swimmers were randomly assigned to either the BFR-RT group (n=8) or the conventional resistance training (RT) group (n=8). Both groups underwent 8 weeks of exercise intervention, with comparative analysis of body composition parameters, morphological measurements, cardiopulmonary endurance indices, and exercise performance metrics before and after the intervention. Results: After 8 weeks of training, both groups showed significant changes in body composition (p>0.05). However, both groups demonstrated marked improvements in lower limb circumference, underwater breath-hold duration, lung capacity, maximum grip strength, 5x10-meter shuttle runs, and 100m freestyle swimming performance (p<0.05), though no statistically significant differences between groups were observed. Conclusion: Both BFR-RT and conventional resistance training effectively enhance cardiorespiratory endurance and exercise capacity in adolescent swimmers over 8 weeks, with no significant difference in efficacy. It is recommended that BFR-RT be adopted as the preferred method for developing strength qualities in adolescent swimmers